Elderly in Pakistan: A Case of Old Age Home/Aafiat, Lahore, Social Welfare Department, Government of Punjab - Din, Nazia Salah ud; Jabeen, Tahira; Batool, Maryam (Pakistan Journal of Humanities and Social Sciences, 2024)
Concern over ageing populations is rising as more healthcare facilities and other services for the elderly are needed, particularly in developing nations. In Pakistan, the loss of the joint family structure that provided older people with protection from their families has left them feeling insecure. Old age homes provide an alternate kind of care to traditional care for the elderly, with those who have no other means of housing or care taking up residence in these residential facilities. The current quantitative study was conducted with the objective to explore the causes of residing elderly in old age home, problems faced by elderly living in residential care and the satisfaction level of elderly regarding the services available for them in the institution. It was a cross sectional study and interviews were conducted with all 25 residents who were present at the time of data collection at the old age home/Aafiat in Lahore. According to the findings of the study mostly respondents were male and they were currently having no source of income. It was also found that there were multiple factors responsible for the respondents to reside in old age home including the absence of a family, financial constraints, physical/mental health issues, physical/verbal abuse faced by respondents, family’ misbehavior and lack of support.